И.И. Казас – редактор газеты «Таврида» - Прохоров, Д.А. (Материалы по археологии, истории и этнографии Таврии, 2002)
В ряду выдающихся представителей отечественной науки второй половины XIX в. одно из почетных мест принадлежит Илье Ильичу Казасу (1833-1912). Блестящий педагог, ученый и общественный деятель, посвятивший всю свою жизнь делу просвещения, стоял у истоков возрождения народного образования татар и караимов. On the of October 1880, the first issue of private newspaper “Tavrida” was published. I.I. Kazas, an outstanding Karaite enlightener and teacher, was its editor and publisher. The newspaper consisted of some sections. The first place was for articles on social and political life of Taurida region (guberniya). Literature section was devoted to ethnography, history and archaeology of Crimea. Here some feuilletons, stories by our and foreign authors. In reference section there were different announcements, railway time-tables. Besides, in the “Tavrida” there were reviews of political events in Russian Empire and in the whole world.